Indistinguishable pattern of amygdala and hippocampus rewiring following tone or contextual fear conditioning in C57BL/6 mice - Pignataro, Annabella; Middei, Silvia; Borreca, Antonella; Ammassari-Teule, Martine (Frontiers in Behavioral Neuroscience, 2013)
Changes in neuronal connectivity occurring upon the formation of aversive memory were examined in C57BL/6 (C57) mice 24h after they were trained for tone and contextual fear conditioning (TFC and CFC). Although TFC and CFC are amenable to distinct learning systems each involving a specific neural substrate, we found that mice trained in the two protocols showed the same increase in spine density and spine size in class I basolateral amygdala and in dorsal hippocampus CA1 pyramidal neurons. Our findings suggest that, because of their remarkably functional hippocampus, C57 mice might engage this region in any fear situation they face. These observations raise a point relevant to aversive memory studies, i.e., how the peculiarity of memory in certain individuals impacts on the components of the fear circuitry. It is suggested that enhanced connectivity in brain regions dispensable for specific forms of learning could considerably increase the resistance of aversive memory traces to treatments aimed at disrupting them.